Private Investment in IDA Countries in the First Half of 2011 was Concentrated in a Few, Large Projects - Nicholas, Alexander (World Bank, Washington, DC, 2013)
In the first semester of 2011, three new projects reached financial closure in the International Development Association (IDA) countries of Lao PDR, Malawi and Zambia, representing investment commitments of US$1.042 billion. Investment in the first semester of 2011 decreased by 39 percent compared with the first semester of 2010, but was roughly on par with investment in the first semester of 2009. In the past five years, Investment in the first semester has generally been over US$1 billion, with the exception of the financial crisis of 2008. By number of projects, activity in 2011 decreased by 70 percent compared with the first semester of 2010 indicating fewer, larger projects. The three projects reaching financial closure were unique in that they were relatively large projects for IDA countries.